Port competition and hinterland connections: Summary and conclusions - OECD; International Transport Forum (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2008)
Maritime freight transport has experienced strong growth and profound change over recent decades. Freight volumes and container traffic in particular have grown with the ntensification of global trade and the geographical dispersion of production. The industrial organization of the sector has evolved rapidly. These changes have rendered the ports business environment more challenging. Many agents along the supply chain have engaged in horizontal and vertical integration of activities. This has lead to more efficiency in the movement of cargo, but has reduced the number of players, with an attendant risk of abuse of market power. The market power of the ports vis-à-vis shippers and shipping companies has become correspondingly weaker. The rapid expansion of trade has led to fast growth of throughput in many ports. As a result, in many large gateway ports, local communities are increasingly concerned about the negative impacts of port activity, including local pollution and congestion. The greenhouse gas emissions generated by freight traffic are also a growing policy concern. This paper explores the economic framework in which potential regulatory intervention to address the issues of competition, air pollution, congestion, greenhouse gas emissions, and financing and provision of infrastructure should be considered.
Keywords: 330; Hafenanlagen; Containerhafen; Seefrachtverkehr; Lieferkette